2004
DOI: 10.1136/pgmj.2004.020446
|View full text |Cite
|
Sign up to set email alerts
|

Management of portal hypertension

Abstract: Treatment of portal hypertension is evolving based on randomised controlled trials. In acute variceal bleeding, prophylactic antibiotics are mandatory, reducing mortality as well as preventing infections. Terlipressin or somatostatin combined with endoscopic ligation or sclerotherapy is the best strategy for control of bleeding but there is no added effect of vasoactive drugs on mortality. Non-selective β-blockers are the first choice therapy for both secondary and primary prevention; if contraindications or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 119 publications
0
8
0
Order By: Relevance
“…Other studies have also detected increased PRA and Ang Ⅱ levels in ALD patients [8,18] . In the initial stages of human cirrhosis, PRA measurements revealed a non-activated or even suppressed circulating RAS [16,18] . In this regard, we have recently found that chronic treatment with propranolol in advanced cirrhotic patients is characterized by marked changes in the precursors of the RAS cascade (renin and Ang Ⅰ) with repercussions in the 2 main components of the RAS [Ang Ⅱ and Ang-(1-7)] in the splanchnic and peripheral circulation [15] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have also detected increased PRA and Ang Ⅱ levels in ALD patients [8,18] . In the initial stages of human cirrhosis, PRA measurements revealed a non-activated or even suppressed circulating RAS [16,18] . In this regard, we have recently found that chronic treatment with propranolol in advanced cirrhotic patients is characterized by marked changes in the precursors of the RAS cascade (renin and Ang Ⅰ) with repercussions in the 2 main components of the RAS [Ang Ⅱ and Ang-(1-7)] in the splanchnic and peripheral circulation [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 displays the Child-Pugh scores [16] of our patients. The primary etiology of the liver disease was established in 21 subjects (87.5%), and included alcoholism, hepatitis C virus, hepatitis B virus and biliary cirrhosis.…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…(2) The strangulated varix, subsequently thromboses and sloughs. Usually up to three bands are applied at each session.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of variceal bleeding is ∼ 30% in patients with compensated cirrhosis and 60% in those with decompensated cirrhosis [26] . Mortality associated with acute variceal bleeding ranges from 5 to 35% depending on patient age and disease severity [27] . Factors predictive of the risk of bleeding include the severity of liver disease as indicated by the Child-Pugh grade, increased variceal size and the presence of red wale markings on the varices [28] .…”
Section: Varices and Bleedingmentioning
confidence: 99%